The influence of ice sheets on temperature during the past 38 million years inferred from a one-dimensional ice sheet-climate model - Stap, Lennert B.; Van De Wal, Roderik S.W.; De Boer, Bas; Bintanja, Richard; Lourens, Lucas J. (Climate of the Past, 2017)
Since the inception of the Antarctic ice sheet at the Eocene-Oligocene transition ( ~34 Myr ago), land ice has played a crucial role in Earth's climate. Through feedbacks in the climate system, land ice variability modifies atmospheric temperature changes induced by orbital, topographical, and greenhouse gas variations. Quantification of these feedbacks on long timescales has hitherto scarcely been undertaken. In this study, we use a zonally averaged energy balance climate model bidirectionally coupled to a one-dimensional ice sheet model, capturing the ice-albedo and surface-height-temperature feedbacks. Potentially important transient changes in topographic boundary conditions by tectonics and erosion are not taken into account but are briefly discussed. The relative simplicity of the coupled model allows us to perform integrations over the past 38 Myr in a fully transient fashion using a benthic oxygen isotope record as forcing to inversely simulate CO 2 . Firstly, we find that the results of the simulations over the past 5 Myr are dependent on whether the model run is started at 5 or 38 Myr ago. This is because the relation between CO 2 and temperature is subject to hysteresis. When the climate cools from very high CO 2 levels, as in the longer transient 38 Myr run, temperatures in the lower CO 2 range of the past 5 Myr are higher than when the climate is initialised at low temperatures. Consequently, the modelled CO 2 concentrations depend on the initial state. Taking the realistic warm initialisation into account, we come to a best estimate of CO 2 , temperature, ice-volume-equivalent sea level, and benthic ^delta; 18 O over the past 38 Myr. Secondly, we study the influence of ice sheets on the evolution of global temperature and polar amplification by comparing runs with ice sheet-climate interaction switched on and off. By passing only albedo or surface height changes to the climate model, we can distinguish the separate effects of the ice-albedo and surface- height-temperature feedbacks. We find that ...